Norwegian student-athletes` motivation for choosing lower secondary sport schools: exploring latent profiles and their relationships with outcomes - Gjesdal, S.; Jordalen, G.; Bjørndal, C. T. (International Journal of Sport and Exercise Psychology, 2025)
Quality of motivation, as reflected in someone`s underlying motivational regulations, plays a pivotal role in shaping the overall experience and outcomes of engagement. A highly relevant context for examining key motivational factors is specialised sport schools at the lower secondary level. Within this unique educational setting, student-athletes face the dual challenge of excelling in both sport and academics, all while navigating the crucial period of adolescent identity development. Success in this demanding environment necessitates high-quality motivation. Surprisingly, there has been a dearth of research investigating the motivation for choosing such specialised schools. To address this, the present study employed a person-centred approach, seeking to identify distinct motivational profiles among students at specialised sport schools. A total of 521 student-athletes (mean age = 13.87, SD = .85), participated in this study. Latent profile analysis revealed the existence of three distinct motivational profiles, which were labelled highly motivated, motivated and unmotivated, respectively. Notably, student-athletes classified within the highly motivated profile exhibited greater levels of enjoyment, vitality and perceived performance when compared to their peers in the other two profiles. The findings reflect positively on specialised sport schools, suggesting that the vast majority of student-athletes who enrol in these institutions do so with a high degree of motivation, a motivation which is also multifaceted. This study contributes valuable insights into student-athletes` motivation underlying their decision to enrol in specialised sport schools.